A study in retail sales person effectiveness - M. Birt; D. Vigar (South African Journal of Business Management, 2002)
Strategic Management theory suggests the importance behavioural alignment of organisational actors with organisational objectives (Robbins, 1998, Hellriegel, et al. 2001). This study utilises Kelly's Personal Construct theory to examine the similarity of constructs held by four groups of actors in a retailing operation, regional managers, store manageress, sales personnel and customers. The study also compares constructs in appropriate company documentation. The results suggest a lack of similarity between the groups and the groups with Company documentation, it is argued that this lack of alignment would have detrimental effects for the organisation.
Keywords: 650